GAME-BASED LEARNING AS AN INTERACTIVE LEARNING MEDIA IN ENGLISH CLASSROOM - Siti Shinta Yulistiyani; Esa Aditya Kurniawan; Vivi Zahiroh; Tri Pujiani (Wiralodra English Journal, 2025)
The rapid growth of computer technology has transformed education, offering new ways to enrich conventional learning processes. This article presents the application of Game-Based Learning (GBL) to improve the teaching of English. GBL integrates fun and learning, appealing to students through game-like approaches that promote communication, problem-solving, and teamwork. This narrative literature review examines how GBL improves student motivation and achievement, particularly in developing speaking competencies. It also delves deeper into the questions of teacher preparedness and technological availability encountered in the application of GBL. The study read studies on theoretical foundations of GBL based on experiential learning and constructivism, as well as its classroom applications in English. The results were that GBL positively influences student motivation and teamwork, reducing anxiety, rendering learning more enjoyable and efficient. However, the success of GBL depends on the coordination of curriculum goals and the overcoming of resource and training barriers. Overall, GBL has the potential to contribute significantly toward English language learning through facilitating an interactive learning setting. Teachers should use GBL to assure learning outcomes through carefully crafted games. Next study should focus on creating effective GBL language skill evaluation materials.